Phylogeny and Density Dynamics of Wolbachia Infection of the Health Pest Paederus fuscipes Curtis (Coleoptera: Staphylinidae) - Chen Ge; Jiayao Hu; Zimiao Zhao; Ary A. Hoffmann; Shuojia Ma; Li Shen; Jie Fang; Jianqing Zhu; Weidong Yu; Weibin Jiang (Insects, 2020)
The maternally inherited obligate intracellular bacteria Wolbachia infects the reproductive tissues of a wide range of arthropods and affects host reproduction. Wolbachia is a credible biocontrol agent for reducing the impact of diseases associated with arthropod vectors. Paederus fuscipes is a small staphylinid beetle that causes dermatitis linearis and conjunctivitis in humans when they come into contact with skin. Wolbachia occur in this beetle, but their relatedness to other Wolbachia, their infection dynamics, and their potential host effects remain unknown. In this study, we report the phylogenetic position and density dynamics of Wolbachia in P. fuscipes. The phylogeny of Wolbachia based on an analysis of MLST genotyping showed that the bacteria from P. fuscipes belong to supergroup B. Quantitative PCR indicated that the infection density in adults was higher than in any other life stage (egg, larva or pupa), and that reproductive tissue in adults had the highest infection densities, with similar densities in the sexes. These findings provide a starting point for understanding the Wolbachia infection dynamics in P. fuscipes, and interactions with other components of the microbiota.